Educational and Employment Opportunities Through Literacy Programs: A Case Study of The Gambia’s Second Chance Education Program (SCEP) - Abdou Barrow (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP),UIN Syarif Hidayatullah Jakarta, 2025)
Abstract. The purpose of this study is to examined the Gambia’s SCEP to understand its contribution to the employability and educational advancement of its beneficiaries. Given that adult literacy have been broadly discussed within human capital framework, I adopt the framework as my analytical lens in this study. The theory presumes that education improves productivity and generates better economic returns. I adopted a qualitative case study design using semi-structured telephone interviews, document review, and beneficiaries’ testimony from website. Additionally, I used analysed secondary data (enrolment and examination result) from the Ministry of Basic and Secondary Education (MoBSE). The study found that SCEP offers some participants an opportunity to reintegrate in formal education and enhance their employment prospect. Most participants had the opportunity to enter into formal workforce, mainly in education as teachers and health (nurse). Additionally, some participants reported pursuing higher education (The Gambia College and The University of the Gambia). Notwithstanding, the study found some challenges potentially limits the program from reaching its full potential, including double-burden, social stigma, gender roles, and resource constraints. The study underscored the transformative potential of SCEP, improving human capital while showing the need for localized intervention strategies to be adopted to address systemic barriers and cultural issues. Moreover, expanding and institutionalizing SCEP may increase its impact on national development and lifelong learning goals. Keywords: Second Chance Education, The Gambia, Economic Return, Adult Literacy, Human Capital. Abstrak. Tujuan penelitian ini untuk mengkaji SCEP di Gambia guna memahami kontribusinya atas peningkatan keterkerjaan dan perkembangan pendidikan para penerimanya. Mengingat literasi orang dewasa telah banyak dibahas dalam kerangka modal manusia, saya mengadopsi kerangka tersebut sebagai lensa analitis dalam penelitian ini. Teori ini berasumsi bahwa pendidikan meningkatkan produktivitas dan menghasilkan keuntungan ekonomi yang lebih baik. Saya menggunakan desain studi kasus kualitatif dengan wawancara semi-terstruktur melalui telepon, telaah dokumen, dan testimoni penerima manfaat dari situs web. Selain itu, saya menganalisis data sekunder (data pendaftaran dan hasil ujian) dari Kementerian Pendidikan Dasar dan Menengah (MoBSE). Hasil penelitian menunjukkan bahwa SCEP memberikan sebagian peserta kesempatan untuk kembali ke pendidikan formal dan meningkatkan prospek kerja mereka. Sebagian besar peserta memperoleh peluang untuk memasuki dunia kerja formal, terutama di sektor pendidikan sebagai guru dan di sektor kesehatan sebagai perawat. Selain itu, beberapa peserta melaporkan melanjutkan pendidikan tinggi di Gambia College dan University of The Gambia. Kendati demikian, penelitian ini menemukan adanya sejumlah tantangan yang berpotensi membatasi program untuk mencapai potensi penuhnya, termasuk beban ganda, stigma sosial, peran gender, dan keterbatasan sumber daya. Studi ini menegaskan potensi transformatif SCEP dalam meningkatkan modal manusia, sekaligus menunjukkan perlunya strategi intervensi yang terlokalisasi untuk mengatasi hambatan sistemik dan persoalan budaya. Lebih jauh, perluasan dan institusionalisasi SCEP berpotensi meningkatkan dampaknya terhadap pembangunan nasional dan tujuan pembelajaran sepanjang hayat. Kata kunci: Pendidikan Kesempatan Kedua, Gambia, Keuntungan Ekonomi, Literasi Dewasa, Modal Manusia.